A eficiência das escolas públicas estaduais do ensino médio regular no Ceará - Dias, José Ricardo Moreira (2014)
This study evaluates the relative technical efficiency of resources / public investment in education in the public schools of the regular high school in the state of Ceará for the year 2012. Employee the model uses the Data Envelopment Analysis (DEA) based on the application of methods linear mathematical programming. The analysis was based on indicators and variables related to expenditures on cost and maintenance of schools, the average daily class hours, the number of computers available to students, the rates of agegrade, approval and notes SPAECE averages. After the construction of the boundary of technical efficiency of these schools, the efficiency scores possible to construct a rank, noting that in 2012, approximately 20% of the surveyed school units were effective in the proposed model.